In-Class Online Discussion Activities to Enhance EFL Learners’ English Self-Efficacy and Language Learning Strategies - Pei-Ling Yang (ASIAN TEFL Journal of Language Teaching and Applied Linguistics, 2016)
The study aims to investigate the effect of in-class online discussion on EFL college low-achievers’ English self-efficacy and their language learning strategies.  It integrates the features of quasi-experimental research to examine whether online discussions would enhance college low-achievers’ English self-efficacy and their learning strategy application.  Two classes of the college learners from one university were randomly recruited in the study.  Two questionnaires (English self-efficacy and language learning strategies) were administered both before and after the intervention.  Besides the descriptive analysis of the learners’ background information, a series of inferential statistics were conducted to demonstrate findings from the quantitative data.  The study results reveal two significant findings.  First, the participants applied language learning strategies more frequently.  Second, the participants had higher levels of English self-efficacy.